1985
DOI: 10.1128/iai.50.3.932-934.1985
|View full text |Cite|
|
Sign up to set email alerts
|

Iron deficiency protects inbred mice against infection with Plasmodium chabaudi

Abstract: Plasmodium chabaudi infections of NFR/N mice made anemic by dietary iron deficiency produced mortalities of 25% (male) and 7% (female) compared with 100% in iron-sufficient controls. When iron-deficient mice convalescing from the primary infection were returned to the normal diet, 100% experienced recrudescent parasitemia. No recrudescence occurred in mice maintained on the iron-deficient diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 12 publications
0
8
2
Order By: Relevance
“…C57BL/6 mice (female, aged 5 wk) were obtained from Kyudo (Tosu, Japan) and BALB/c nu/nu (nude) mice from CLEA (Japan). IDA mice were bred as described elsewhere 32. Briefly, C57BL/6 mice, or nude mice, were fed either a control or iron‐deficient diet for 10 wk.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 mice (female, aged 5 wk) were obtained from Kyudo (Tosu, Japan) and BALB/c nu/nu (nude) mice from CLEA (Japan). IDA mice were bred as described elsewhere 32. Briefly, C57BL/6 mice, or nude mice, were fed either a control or iron‐deficient diet for 10 wk.…”
Section: Methodsmentioning
confidence: 99%
“…When the iron-deficient mice were then fed iron-sufficient foods, they fell victim to recrudescent parasitemia. 48 More recent experimental evidence refutes the earlier nutritional immunity hypothesis and concludes no significant protection of iron deficiency in young rats. 49 Other evidence suggests that iron deficiency impairs immune responses, including T lymphocyte production and activity, natural killer cell activity, and neutrophil function.…”
Section: Introductionmentioning
confidence: 80%
“…Multiple studies have attempted to evaluate the benefit of iron supplementation in malaria-endemic areas [19,[115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Some studies reported that iron supplementation increased the risk of developing or reactivating malarial illness [19,115,118], while others reported no significant adverse effects [123,125,135]. Experiments with rodent malaria have also yielded conflicting results [135][136][137][138].…”
Section: Ironmentioning
confidence: 99%
“…Some studies reported that iron supplementation increased the risk of developing or reactivating malarial illness [19,115,118], while others reported no significant adverse effects [123,125,135]. Experiments with rodent malaria have also yielded conflicting results [135][136][137][138]. To clarify this issue, a systematic review and meta-analysis of placebo-controlled trials of iron supplemen-tation in humans was recently completed [139].…”
Section: Ironmentioning
confidence: 99%